Real Income, Expenditure Proportionality, and Frisch's "New Methods of Measuring Marginal Utility" - Burk, Abram (Review of Economic Studies, 1936)
Journal Article Real Income, Expenditure Proportionality, and Frisch's "New Methods of Measuring Marginal Utility" Get access Abram Burk Abram Burk Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 1, October 1936, Pages 33–52, https://doi.org/10.2307/2967658 Published: 01 October 1936